POTENTIAL OF CARBON STORAGE IN ANGSANA PLANT (Pterocarpus indicus Willd) IN ILIR BARAT I DISTRICT, PALEMBANG CITY - Rosianty, Yuli; Waluyo, Efendi Agus; Himawan, Muhammad Surya Ganda (Universitas Muhammadiyah Palembang, 2021)
This aims of the study is to determine the potential for carbon deposits and uptake in Angsana (Pterocarpus indicus Willd) tree species. This research was carried out in December 2019. To determine the potential for carbon storage, the Allometric Equation formula was used to estimate biomass stored in it. A half of the biomass is carbon content stored. The results of this study showed that the largest estimation of carbon storage in green space of Ilir Barat I District at the point of observation of GOR / PSCC with a total carbon content of 17,999 tons / ha with an individual number of 23 species of Angsana plants (Pterocarpus indicus Willd). For the District of Ilir Barat I in the City of Palembang, it is expected to increase the number of Angsana (Pterocarpus indicus Willd) plants because these plants can absorb enough carbon and have strong roots